Accuracy of Magnetic Resonance Imaging in the Diagnosis of Acetabular Chondral Delamination in Femoroacetabular Impingement. Issue 8 (24th August 2022) - Gao, Guanying; Dong, Hanmei; Wang, Jianquan; Ao, Yingfang; Xu, Yan
Background: Currently, there is no consensus regarding the accuracy of magnetic resonance imaging (MRI) in the detection of acetabular chondral delamination (ACD) in patients with femoroacetabular impingement (FAI), and, correspondingly, the preoperative diagnosis of ACD remains challenging. Hypothesis: It was hypothesized that MRI would have relatively high accuracy in detecting ACD in patients with FAI. Study Design: Cohort study (diagnosis); Level of evidence, 2. Methods: We retrospectively evaluated patients who attended the sports medicine clinic of our department and underwent arthroscopic surgery for the diagnosis of FAI between January 2018 and December 2020. All patients underwent preoperative 3.0-T MRI. ACD was evaluated by 2 raters on 3.0-T MRI scans, and interrater and intrarater reliability was assessed. Sensitivity, specificity, accuracy, positive predictive value (PPV), and negative predictive value (NPV) of MRI for diagnosis of ACD were calculated, using arthroscopic surgery as the standard. Results: A total of 233 patients (mean age, 37.4 years; 99 male and 134 female) were included in this study. The presence of ACD in 101 (43.3%) patients was confirmed during hip arthroscopy. The intraobserver reliability of both of the observers in detecting ACD using 3.0-T MRI scans was almost perfect (observer 1, kappa coefficient [κ] = 0.909 [95% CI, 0.854-0.964]; observer 2, κ = 0.937 [95% CI, 0.890-0.984]), and the interobserver reliability between the observers (κ = 0.801 [95% CI, 0.723-0.879]) was substantial. The overall sensitivity, specificity, PPV, and NPV of preoperative MRI to detect ACD were 83.7%, 82%, 74.2%, and 89.1%, respectively. Conclusion: It was found that 3.0-T MRI had a relatively high sensitivity, specificity, PPV, and NPV for diagnosis of ACD in patients with FAI and could be a reliable method of diagnosing ACD preoperatively.